Revision of informant plausibility in multi-agent system - Simari, Guillermo Ricardo (2001)
Within the context of multi-agent systems, an agent may often find itself in a position where it receives information through informants. These informants are independent agents who have their own interests and, therefore are not necessarily completely reliable. It is natural for an agent to be more inclined to believe one informant over another, especially if the informant has provent itself reliable over a period of time. This paper proposes the organization of the informants into a partial order with compares the plausibility of the relevant informants. This partial order need not remain static throughout the agent's lifespan. The agent may choose to update its partial order relation to reflect a new perception of informants plausibility. Therefore this paper also proposes the application of change operators, not to the beliefs themselves, but to the partial order. These operators are used to alter the structure of relative credibility of the informants. These operators are characterized through postulates and construction is provided for them.